PENGARUH KINERJA PELAYANAN, ATRIBUT PRODUK, DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA PENONTON BIOSKOP CINEMA XXI AYANI PONTIANAK) - DILAVENTI B11110103, ANDARISKI NOKA (Jurnal Manajemen Update, 2014)
This research aimed to analyze the influence of service performance, product attribute, perceived price toward customer loyalty of Cinema XXI Ayani Pontianak. This research was designed as an associative causal. The population of this research is the customer of Cinema XXI Ayani Pontianak who have been watching at least 3 times and those who buy weekday tickets (Monday to Friday). This research was using purposive sampling, then elected a sample size of 100 people. The analysis technique used multiple linier regression analysis by SPSS version 20.0. The results based on multiple linier regression analysis showed that service performance, product attribute, perceived price influence significantly to the customer loyalty of Cinema XXI Ayani Pontianak, with the significance of value 0.000 and R2 of 45,3%, while the rest amounted 54,7% were other factors which are not examined in this study. Keywords : service performance, product attribute, perceived price, and customer loyalty